Pengembangan Sistem Otomatis Penghematan Air dengan Sensor Ultrasonik pada Perangkat Cuci Tangan - Saputri, Fahmy Rinanda; Pranata, Nicholas; Linelson, Richardo; Lavenia, Tanashia (Jurnal Komunikasi, Sains dan Teknologi, 2023)
The ongoing COVID-19 pandemic has highlighted the critical importance of maintaining hand hygiene to prevent virus transmission. The virus can be present in carriers who may not display symptoms, making regular handwashing a crucial preventive measure. However, excessive water consumption during handwashing can strain water resources, particularly in regions facing water scarcity. This research presents an innovative system that combines effective handwashing with water conservation. The proposed system utilizes Arduino UNO, along with additional components such as resistors, ultrasonic sensors, an LCD, and LEDs, to guide individuals through a recommended approximately 20-second handwashing process. An ultrasonic sensor is employed to detect hand proximity, while an LCD provides instructions, and LEDs change color to signal the completion of the handwashing duration.